(E)-Benzyl 3-(3-nitrobenzylidene)dithiocarbazate - Hai-Liang Zhu (Acta Crystallographica Section E, 2009)
In the title compound, C15H13N3O2S2, the dihedral angle between the aromatic rings is 87.8 (2)°. In the crystal, inversion dimers occur linked by pairs of N—H...S hydrogen bonds.